2021
DOI: 10.3390/foods11010052
|View full text |Cite
|
Sign up to set email alerts
|

Textural, Sensory and Volatile Compounds Analyses in Formulations of Sausages Analogue Elaborated with Edible Mushrooms and Soy Protein Isolate as Meat Substitute

Abstract: In this study, edible mushroom and soybean protein isolate (SPI) were used to prepare a fibrous meat analogue using thermos-extrusion and the extruded mushroom-based meat analogue as meat replacer was further developed with different formulations in fabricating sausage analogues. The effect of water content (35%, 70% and 100%), three types of edible mushroom (Lentinus edodes, Pleurotus ostreatus, Coprinus comatus and a mixture of equal proportions) and their amounts (from 15% to 100%) on the physicochemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 38 publications
0
29
0
2
Order By: Relevance
“…The bibliometric analysis revealed that the 84 papers included in the systematic review were published in 38 journals between 1972 and 2022. It was revealed that the most frequent journals chosen by the authors were Foods with 15 articles [ 14 , 15 , 24 , 41 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ], followed by Journal of Food Science with nine articles [ 11 , 20 , 25 , 60 , 61 , 62 , 63 , 64 , 65 ]. Because the journals were indexed by both Scopus and Web of Science databases, they were all of high quality, and most were placed in Quartile 1 or 2 (see Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The bibliometric analysis revealed that the 84 papers included in the systematic review were published in 38 journals between 1972 and 2022. It was revealed that the most frequent journals chosen by the authors were Foods with 15 articles [ 14 , 15 , 24 , 41 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ], followed by Journal of Food Science with nine articles [ 11 , 20 , 25 , 60 , 61 , 62 , 63 , 64 , 65 ]. Because the journals were indexed by both Scopus and Web of Science databases, they were all of high quality, and most were placed in Quartile 1 or 2 (see Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of meat analogues, several researchers developed the products directly as whole muscle meat (mostly from extrusion) with or without some added ingredients [ 24 , 49 , 51 , 52 ], but others referred to meat analogues as restructured meat products such as Turkish dry fermented sausages (“sucuk”) from wheat bulgur [ 69 ], SPI sausage [ 79 ], and edible mushroom sausages [ 57 , 109 ]. The study by Rousta et al [ 56 ], who investigated the culture of the fungus on oat flour and its use in the development of burger patties, demonstrated the productive potential of the fungus for the manufacture of nutrient-dense foods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mushrooms cannot be considered as a significant source of proteins compared to meat sources, even though they are a part of human nutrition mainly because of their taste [ 68 ]. Other authors, however, believe that mushrooms may play an important role in meat analogs by providing nutrients and promoting the development of sensory properties such as appearance, texture, and taste of the product [ 69 ]. The use of mushrooms as an alternative source of protein in the human diet is not a new concept.…”
Section: Protein Sources and Their Roles In Meat-alternative Productsmentioning
confidence: 99%